1998
DOI: 10.1128/aac.42.5.1028
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Susceptibilities of Aerobic and Facultative Non-Spore-Forming Gram-Positive Bacilli to HMR 3647 (RU 66647) and 14 Other Antimicrobials

Abstract: The comparative in vitro activity of the ketolide HMR 3647 (RU 66647) and those of structurally related macrolide-lincosamide-streptogramin compounds (erythromycin, roxithromycin, azithromycin, clarithromycin, josamycin, lincomycin, pristinamycin, and quinupristin-dalfopristin) as well as those of benzylpenicillin, doxycycline, vancomycin, teicoplanin, levofloxacin, and rifapentine against 247 aerobic and facultative non-spore-forming gram-positive bacilli were determined by an agar dilution method. The ketoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 16 publications
0
12
0
4
Order By: Relevance
“…The same applies to the intrinsic resistome identified in 103S (9/10 β-lactamases, 5/5 aminoglycoside phosphotransferases and 4/4 multidrug efflux systems were conserved in all strains) (supplementary table S2, Supplementary Material online). Indeed, in vitro resistance to a number of antimicrobials, particularly β-lactams and quinolones, has been observed in 103S (Letek et al 2010) and reported in the literature for R. equi (Nordmann and Ronco 1992; Mascellino et al 1994; Soriano et al 1998; Makrai et al 2000; Jacks et al 2003; Jones and Goodfellow 2012). …”
Section: Resultsmentioning
confidence: 97%
“…The same applies to the intrinsic resistome identified in 103S (9/10 β-lactamases, 5/5 aminoglycoside phosphotransferases and 4/4 multidrug efflux systems were conserved in all strains) (supplementary table S2, Supplementary Material online). Indeed, in vitro resistance to a number of antimicrobials, particularly β-lactams and quinolones, has been observed in 103S (Letek et al 2010) and reported in the literature for R. equi (Nordmann and Ronco 1992; Mascellino et al 1994; Soriano et al 1998; Makrai et al 2000; Jacks et al 2003; Jones and Goodfellow 2012). …”
Section: Resultsmentioning
confidence: 97%
“…The profiles of antimicrobial susceptibility of corynebacteria, including Coryne pseudodiphtheriticum, are not frequently predictable (Riegel et al 1996;Lagrou et al 1998;Soriano et al 1998;Camello et al 2003;Van Enk 2004). Except for the unvarying activity of vancomycin and teicoplanin against Coryne.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to macrolides, clindamycin, trimethropim ⁄ sulphamethoxazole and chloramphenicol was observed in some opportunities (Gutierrez-Rodero et al 1999;Chudnicka et al 2003;Szmygin-Milanowska et al 2003). The emergence of antimicrobial resistance among Corynebacterium species has also been described to penicillin and other b-lactam agents (Riegel et al 1996;Lagrou et al 1998;Soriano et al 1998;Janda 1999;Camello et al 2003). In the present study, the percentage of resistance to penicillin and ampicillin ranged from 38AE9% to 44AE2%.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic susceptibility assays with C. urealyticum DSM7109 revealed high minimum inhibitory concentrations (MICs) for the macrolide erythromycin (>128 g ml −1 ) and the lincosamide lincomycin (>256 g ml −1 ). It is therefore conceivable that erm(X) confers the high resistance levels for macrolides, lincosamides, and the ketolide telithromycin that were observed in clinical C. urealyticum strains in several studies (García-Rodriguez et al, 1991;Soriano et al, 1995Soriano et al, , 1998Martínez-Martínez et al, 1998).…”
Section: Antibiotic Resistance Determinants Of the C Urealyticum Dsmmentioning
confidence: 98%
“…Encrusted cystitis may require endoscopic resectioning of encrustations and antibiotic therapy for permanent cure (Funke et al, 1997;van Hooland et al, 2005). The majority of C. urealyticum strains are, however, highly resistant to a large number of antibiotics, including ␤-lactams, aminoglycosides, and macrolides (García-Rodriguez et al, 1991;Soriano et al, 1995;Martínez-Martínez et al, 1998), although the glycopeptides vancomycin and teicoplanin remain universally active against these isolates (Soriano et al, 1991(Soriano et al, , 1998Lagrou et al, 1998). It has been suggested that the appearance of multiresistant C. urealyticum strains is favored by the use of antibiotics in hospital settings and that these strains are likely to be acquired by inpatients directly from the bacterial flora present in the hospital environment (Garcia-Bravo et al, 1996).…”
Section: Introductionmentioning
confidence: 99%